Mencari Agama Baru (Studi Terhadap Munculnya Sekte-Sekte Agama) - Waryono Abd. Ghofur (Al-Jami'ah Research Centre, 1998)
Every religion born in the society always has its own attraction and fascination, especially if they are seen from the outward perspective of the religion. The fascination offered by the religion is basically promised claims or doctrines which give a covenant as well to their adherents. one thing that psychologically can fulfill people's desire and makes him satisfied to live in and together with it. They are fascination and claims which become